Foot Exercise Implementation in a Patient with Physical Mobility Impairment due to Diabetes Mellitus - Aulia, Adinda; Fitriani, Ade; Hamdani, Dadi (Yayasan Inspirasi El Burhani, 2024)
Introduction: : Diabetes Mellitus (DM) is a non-communicable disease that continues to show an increase globally, including in Indonesia. According to WHO data in 2016, as many as 422 million adults in the world have diabetes. This disease is caused by insulin deficiency, either relatively or absolutely, and often causes complications such as peripheral neuropathy which causes decreased sensation in the feet. One of the steps to prevent these complications is through foot exercises. Foot exercises are special physical exercises for diabetics that aim to prevent wounds, improve blood flow, strengthen small muscles in the feet, and prevent deformities due to nerve disorders and muscle weakness. Objective: This case study aims to implement foot exercises in patients with impaired physical mobility with diabetes mellitus. Method: This research uses a descriptive method in the form of a case study with a nursing approach which includes assessment, nursing diagnosis, nursing care plan, nursing implementation, and nursing evaluation. Data collection was done by interview, observation, physical examination, and documentation. Result: After the assessment, it is known that Mrs.D obtained a nursing diagnosis of impaired physical mobility associated with decreased muscle strength with diagnosis number D.0054, after being given implementation in the form of foot exercises for 3 days with a duration of 5-7 minutes a day, the nursing problem of impaired physical mobility of the client is partially resolved which is characterized by increased muscle strength with muscle strength values on the right lower extremity 4 and the left 5. Conclusion: The implementation of foot exercises has proven to be useful for reducing movement limitations and increasing muscle strength in all extremities, the benefits of this foot exercise will be maximized if done gradually and periodically.